Reviews on design and development of unmanned aerial vehicle (drone) for different applications - Aabid, Abdul; Perveez, Bisma; Perveen, Nagma; Khan, Sher Afghan; Raheman, Md Abdul; Zayan, Jalal Mohammed; Shabbir, Omer (The Scientific Press, 2022)
The modern designs and their developments are essential based on their application; hence, UAV's can be built with specific design and loading conditions. In this review for the first, a basic idea about UAVs considering required engineering aspects has been studied. The existing literature has been critically reviewed to extract the fundamental idea of UAVs such as fabrication method, design, materials, structures, classifications, and so on. The UAVs in multiple applications such as the use of drones by law enforcement agencies, military, search, and rescue missions, etc. were highlighted. Based, on the existing work in drone technologies a critical analysis was made to extract the research gap and recommended accordingly. As result, with these guidelines, the drones can be built for specific purposes and applications like COVID-19 pandemic missions, policing surveillance, and large-scale sanitation of remote access areas